2020
DOI: 10.1159/000509039
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Stem Cells with Hyperthermia: Translational Relevance in Cancer Patients

Abstract: <b><i>Background:</i></b> Tumor recurrences or metastases remain a major hurdle in improving overall cancer survival. In anticancer therapy, some patients inevitably develop chemo-/radiotherapy resistance at some point. Cancer stem cells are the driving force of tumorigenesis, recurrences, and metastases, contributing also to the failure of some cancer treatments. <b><i>Summary:</i></b> Emergent evidence suggests that stem cell diseases are at the base of human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Finally, HT inhibits tumor angiogenesis through two different mechanisms. On the one hand, it directly damages endothelial cells because of the absorption of the electric field related thermal energy in the extracellular liquid, with a subsequent temperature gradient between the extra-and intracellular compartments, which threatens and/or destroys cancer cell membranes (67,68). On the other hand, it is well known that hypoxic tumor microenvironment stimulates the expression of hypoxiainducible factor-1 (HIF-1), which is the main VEGF inducer, the most powerful angiogenic factor.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, HT inhibits tumor angiogenesis through two different mechanisms. On the one hand, it directly damages endothelial cells because of the absorption of the electric field related thermal energy in the extracellular liquid, with a subsequent temperature gradient between the extra-and intracellular compartments, which threatens and/or destroys cancer cell membranes (67,68). On the other hand, it is well known that hypoxic tumor microenvironment stimulates the expression of hypoxiainducible factor-1 (HIF-1), which is the main VEGF inducer, the most powerful angiogenic factor.…”
Section: Introductionmentioning
confidence: 99%
“…Its therapeutic potential has been demonstrated either alone or in combination with other standard treatments. [70][71][72] The limited number of studies have focused on the factors released from hyperthermia-stimulated MSCs, and few studies have demonstrated their antitumoral effects on solid cancers post determination of the potential of MSCs in cancer therapy. 72,73 Park et al 72 have reported that MSCs stimulated by hyperthermia could increase the effectiveness of chemotherapeutic drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperthermia is the process of raising the temperature on the tumor tissue up to 40−43°C, resulting in the induction of cancer cell death. Its therapeutic potential has been demonstrated either alone or in combination with other standard treatments 70–72 . The limited number of studies have focused on the factors released from hyperthermia‐stimulated MSCs, and few studies have demonstrated their antitumoral effects on solid cancers post determination of the potential of MSCs in cancer therapy 72,73 .…”
Section: Discussionmentioning
confidence: 99%
“…Cellular responses to thermal stimuli range from activation of pathways that promote survival to programmed cell death to remove damaged cells. 26 When the thermal stimulus is strong enough, the cell activates the death signaling pathway. 27 During heat stress, cells rapidly upregulate the transcription and translation of HSP to protect cells from protein aggregation and degradation.…”
Section: Otud7b Knockdown Impaired Hyperthermia-induced Inhibition Of...mentioning
confidence: 99%